Identifying Functional Labour Market Areas in New Zealand: A Reconnaissance Study Using Travel-to-Work Data - Kerry L. Papps; James O. Newell (Institute for the Study of Labor (IZA), 2002)
To date, analysis of the spatial dimension of New Zealand labour markets has been limited to administrative, rather than appropriately-defined functional, geographic units. This paper presents a preliminary classification of New Zealand into local labour market areas using area unit travel-to-work data from the 1991 Census of Population and Dwellings and drawing on the regionalisation method of Coombes et al. (1986). After assessing the robustness of the preferred set of local labour market areas, the paper provides some illustrative labour market statistics for these zones. Migration between labour market areas is most likely to be accompanied by changes in job, whereas moves within a labour market are largely assumed to be non-work motivated. As a result, this study provides a more appropriate spatial unit of analysis than any administrative classification for studying migration at a subnational level.
Keywords: R12; J61; R23; 330; Geographic labour mobility; regional migration; regional labour markets; Regionaler Arbeitsmarkt; Regionale Arbeitsmobilität; Binnenwanderung; Berufsverkehr; Neuseeland